The Role Of Spiritual Security In Protecting Youth From Internet Threats (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the increasing information threats in the Internet space, their impact on the consciousness of young people, and the role of spiritual security in overcoming them. It is noted that the rapid growth of digital information flows directly affects the worldview, values, and social behavior of youth. The study examines risk factors such as harmful content, manipulative information, and virtual addiction, and highlights the theoretical and practical foundations of strengthening spiritual immunity against them. In addition, the importance of the education system, the educational role of the family environment, mass media, and state policy in ensuring spiritual security is substantiated